Simulation of the Raman spectroscopy of multi-layered carbon nanomaterials. Issue 44 (1st November 2018) - Tailor, Pritesh M.; Wheatley, Richard J.; Besley, Nicholas A.
Abstract : A empirical potential based model for simulating the Raman spectroscopy of layered carbon nanomaterials is introduced. Abstract : Multi-layered carbon nanomaterials can have an important role in modern nanotechnology. Raman spectroscopy is a widely used analytical technique that is used to characterise the structure of these materials. In this work, an approach based upon an empirical potential for the simulation of the Raman spectroscopy of carbon nanomaterials [P. M. Tailor, R. J. Wheatley and N. A. Besley, Carbon, 2017, 113, 299–308] is extended through the addition of a term to describe the van der Waals interaction between layers of sp 2 hybridised carbons. The resulting model accurately describes the properties of the shearing modes of few layer graphene and is used to characterise the low frequency modes of multi-walled carbon nanotubes and carbon nanofibres.